Medication-Related Osteonecrosis of the Jaw (MRONJ): A Review of Pathophysiology, Risk Factors, Preventive Measures and Treatment Strategies - Raed AlRowis; Abdulmalik Aldawood; Mohammed AlOtaibi; Essam Alnasser; Ibrahim AlSaif; Abdullah Aljaber; Zuhair Natto (Elsevier, 2022)
Medication-related osteonecrosis of the jaw (MRONJ) is a major problem that can occur in people taking certain medications such bisphosphonates and denosumab. It can be used to treat osteoporosis or cancer. Bisphosphonate exposure, dental diseases and procedures, age, sex, anatomical factors, medical issues, and hereditary factors are all variables that enhance the risk of MRONJ. Even though MRONJ and antiresorptive medications have a close association, the pathophysiology of MRONJ is unknown. Careful dental preparation and oral hygiene instructions significantly minimize the risk of osteonecrosis of the jaw (ONJ). It is ideal to start antiresorptive treatment after the completion of required dental treatment; it is not contraindicated and carries low risk in patients who are on oral antiresorptive medications for less than three years. Drug holidays are one proposed solution to address MRONJ. However, there is still inadequate evidence to support their effectiveness. The objectives of this literature review are to recognize the main diagnostic principles and risk factors and to review the pathophysiology, protective procedures and treatment modalities related to MRONJ.The following topics are covered in the review: epidemiology, diagnostic criteria, risk factors, pathogenesis and mechanism, MRONJ staging and symptoms, clinical and radiographic findings, treatment strategies, prevention and drug holiday.